2022
DOI: 10.5713/ab.21.0561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactoferrin on ram sperm motility after cryopreservation

Abstract: Objective:The objective of this study was to analyse the differentially abundant proteins caused by freeze-thawing of ram sperm and explore candidate proteins of interest for their ability to improve ram sperm cryopreservation outcomes in vitro .Methods: Sperm were from three mature Dorper. Fresh and frozen sperm proteins were extracted, and the differentially abundant proteins were analysed by mass spectrometry (MS).Among these proteins, lactoferrin(LTF) was selected to be added before cryopreservation.Next, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Kobayashi et al reported that the addition of Lf can effectively improve sperm activity and prolong the survival time of frozen-thawed semen after thawing, because Lf maintains the integrity of sperm plasma membrane and reduces the level of reactive oxygen species (ROS) (74). This has also been reported in horses (75), goats (76), and porcine (77).…”
Section: Application Of Lactoferrin In Other Industriesmentioning
confidence: 95%
“…Kobayashi et al reported that the addition of Lf can effectively improve sperm activity and prolong the survival time of frozen-thawed semen after thawing, because Lf maintains the integrity of sperm plasma membrane and reduces the level of reactive oxygen species (ROS) (74). This has also been reported in horses (75), goats (76), and porcine (77).…”
Section: Application Of Lactoferrin In Other Industriesmentioning
confidence: 95%
“…The exact function of LTF in the canine reproductive system is not known, but since it is present in high amounts, it must be important for canine reproductive functions. The addition of LTF to a cryoprotective extender can significantly improve the function of frozen ram sperm [ 66 ].…”
Section: Protein Markersmentioning
confidence: 99%
“…Such modifications, indicative of biomedical and structural stress experienced by sperm, ultimately result in reduced post-thaw quality (Tamburrino et al 2023). Furthermore, cryopreservation significantly impacts the abundance of various proteins in frozen-thawed ram sperm, with some protein levels increasing while others decrease (Su et al 2022). This process also alters the protein profile of ram sperm during in vitro capacitation, affecting sperm capacitation at the molecular level (Peris-Frau et al 2019).…”
Section: Ram Sperm Protein Profilementioning
confidence: 99%